Safety and efficacy of intravenous combination sedatives in the ED - Li, Siu Fai; Kumar, Amy; Thomas, Susan; Sorokina, Yelena; Calderon, Vanessa; Dubey, Elizabeth; Lee, Lani; Gustave, Ludmilla (The American journal of emergency medicine, 2013)
The objective of the study is to determine the safety of intravenously administered combination sedatives in the emergency department (ED). This was a retrospective study of alcohol-intoxicated patients in the ED. We examined the incidence of adverse events in agitated patients who received combination sedatives intravenously and compared the efficacy of combination sedatives and single-agent sedatives. Of 1300 patient visits, there was a single adverse event, a dystonic reaction, in the combination sedative group, for an adverse event rate of less than 1%. Patients who received combination sedatives were less likely to require a second dose of sedative medication than patients who received a single-agent sedative (21% vs 44%). Combination sedatives appear to be safe when administered intravenously in the ED. Combination sedatives may be more effective than single-agent sedatives in agitated alcohol-intoxicated patients.